Pengaruh Persepsi Nasabah dan Margin terhadap Keputusan Pengambilan Pembiayaan Griya di Bank BSI KCP Bandung Majalaya - Pebrianti, Silvia; Nasution, Ade Iskandar (Ma'soem University, 2024)
Based on the results of observations, this research was motivated by a lack of understanding of customers about margins, giving rise to customer perceptions that margins in Islamic banks are the same as interest in conventional banks.This study aims to determine how much influence customer perceptions and margins have on the customer's decision to finance griya at Bank BSI KCP Bandung Majalaya.The type of research is quantitative associative. The type of data used is primary data processed using statistical applications, and using data collection techniques in the form of observation, interviews, literature studies, and questionnaires.The population is home financing customers in 2022 with a sample of 58 people. The results showed that customer perception had a significant effect of 39.1% on griya financing decisions, margin had a significant effect of 37.1% on griya financing decisions, and simultaneously customer perceptions and margins had a significant effect of 39.1% on griya financing decisions at Bank BSI KCP Bandung Majalaya.